Stability and partitioning of β-carotene in whey protein emulsions during storage. Issue 11 (18th September 2017) - Fahmi Wan Mohamad, W. A.; McNaughton, D.; Buckow, R.; Augustin, M. A.
Abstract : Raman spectra of β-carotene in a droplet O/W emulsion, with bands originating from vibrations of the isoprene units of β-carotene molecules. Abstract : Varying the β-carotene (0.1–0.3 g kg −1 ) and whey protein isolate (WPI) (2–20 g kg −1 ) concentrations in an oil-in-water (O/W) emulsion influenced the partitioning and stability of β-carotene upon 30 d storage at 25 and 40 °C. The total β-carotene in the emulsion was extracted with a solvent and quantified using UV/visible spectroscopy. The β-carotene in oil phase was obtained using in situ Raman micro-spectroscopy. The β-carotene in the aqueous phase was obtained by difference. Increasing β-carotene concentration resulted in increased partitioning of β-carotene into the aqueous phase whereas increasing WPI concentration had the opposite effect. With all freshly made emulsions, there was a higher proportion of β-carotene found in the oil phase. At the end of the storage period, the higher proportion and concentration of β-carotene was in the aqueous phase. This suggested that oxidation of β-carotene occurred faster in the oil phase and that WPI in the aqueous phase protected β-carotene against oxidation. This work informs the formulation of protein-based emulsions for the delivery of β-carotene.